Profitabilitas Memoderasi Hubungan Corporate Social Responsibility dan Capital Intensity Terhadap Agresivitas Pajak - Vincy Herdalaksmi Hendrilestari; Agoestina Mappadang; Jamaludin Iskak; Jusuf Luther Mappadang (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2023)
This study aims to understand the impact of corporate social responsibility on tax aggressiveness, the effect of capital intensity on tax aggressiveness, and explore the role of profitability as a moderating variable that can sharpen/weaken the relationship between CSR and tax aggressiveness and the relationship between capital intensity and tax aggressiveness. This study belongs to quantitative research using moderated regression analysis (MRA) using SPSS version 26, this approach uses annual reports of companies listed on the Indonesia Stock Exchange from 2017-2021 with 60 objections. Provisions obtained from the data analysis and discussion that has been carried out, it can be concluded that the CSR variable has a significant negative effect on tax aggressiveness, the capital intensity variable has a significant negative effect on tax aggressiveness, the profitability variable weakens the relationship of CSR to tax aggressiveness, and profit variability weakens the relationship between capital intensity and tax aggressiveness.